Identification and functional analyses of a cell-death inhibitor encoded by guinea pig cytomegalovirus gp38.1 in cell culture and in animals. (11th December 2020) - Noguchi, Kazuma; Majima, Ryuichi; Takahashi, Keita; Iwase, Yoshihiko; Yamada, Souichi; Satoh, Keisuke; Koshizuka, Tetsuo; Inoue, Naoki
Abstract : Cytomegaloviruses (CMVs) employ an array of strategies designed to interfere with host defence responses against pathogens. Studies on such evasion mechanisms are important for understanding the pathogenesis of CMV diseases. Although guinea pig CMV (GPCMV) provides a useful animal model for congenital CMV infection, its evasion strategies are not fully elucidated. Here, we analysed a genome locus that may encode gene products for the GPCMV evasion mechanisms and found the following. (1) RACE analyses identified five transcripts in the GP38-gp38.4 locus, one of which was a spliced product encoding gp38.1. Similarities in the splicing pattern and gene position of gp38.1 to human CMV UL37 and its exon 1 encoding vMIA (viral mitochondria-localized inhibitor of apoptosis) suggest that the gp38.1 gene encodes an apoptosis inhibitor. (2) In a transient transfection assay, gp38.1 localized in the mitochondria and relocated BAX from the cytoplasm to the mitochondria, although its co-localization with BAK was not evident. Further, the expression of gp38.1 partially reduced staurosporine-induced apoptosis. (3) GPCMV defective in the gp38.1 ORF (Δ38.1) and the virus that rescues the defect (r38.1) were generated. Guinea pig fibroblast cells infected with Δ38.1 died earlier than r38.1-infected cells, which resulted in the lower yields of Δ38.1. (4) In animals, viral loads in the spleens of r38.1-infected guinea pigs were higher than those in the spleens of Δ38.1-infected animals. In conclusion, although GPCMV gp38.1 exerts a vMIA-like function, its inhibitory effect was not robust, suggesting the presence of additional inhibitory molecule(s), such as a BAK-specific inhibitor.